2017
DOI: 10.1111/jce.13333
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term safety and efficacy of left atrial appendage closure with the WATCHMAN device in patients with small left atrial appendage ostia

Abstract: LAA closure with the WATCHMAN device can be successfully and safely achieved in patients with a maximal LAA ostial width < 17 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
3
7
0
Order By: Relevance
“…29 The only published study concerning LAAC in patients with a small LAA only had shortterm follow-up results. 9 In our study, the annual stroke risk in the small LAA group was slightly higher than that in the indicated LAA group (1.1/100 person-years vs. 0.3/100 person-years) but comparable to prior investigations. Therefore, LAAC with the Watchman device for stroke prevention in patients with a small LAA orifice may be efficient.…”
Section: Safety and Efficacy Of Laac In Patients With Small Laasupporting
confidence: 90%
See 1 more Smart Citation
“…29 The only published study concerning LAAC in patients with a small LAA only had shortterm follow-up results. 9 In our study, the annual stroke risk in the small LAA group was slightly higher than that in the indicated LAA group (1.1/100 person-years vs. 0.3/100 person-years) but comparable to prior investigations. Therefore, LAAC with the Watchman device for stroke prevention in patients with a small LAA orifice may be efficient.…”
Section: Safety and Efficacy Of Laac In Patients With Small Laasupporting
confidence: 90%
“…No pericardial effusion, device embolization, or stroke/TIA occurred periprocedurally in the study of Venkataraman et al 9 and the present investigation. In the EWOLUTION study, the device oversizing percentage was over 30% in nearly 1/3 patients, indicating that overcompression rate of over 20% was not uncommon in clinical practice.…”
Section: Safety and Efficacy Of Laac In Patients With Small Laasupporting
confidence: 49%
“…9 Small case series and cohort studies support the feasibility of using Watchman 2.5 for very small ostia ,17 mm or in failed surgical LAA ligation with narrow necks, whereas cases with ostia .31 mm would be at high risk for device embolization. 10,11 Anterior chicken wing anatomy often poses an anatomic challenge to LAAC regardless of width with an increased risk of pericardial effusion and cardiac perforation. 12 The Watchman FLX device is a self-expanding nitinol frame with a permeable polyester fabric covering the atrial facing surface and 18 peripheral fixation anchors in 2 layers designed to improve stability and reduce embolization risk in comparison to the Watchman 2.5 device.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that LAA ostia smaller than those specified in the directions for use (o17 mm) for WATCHMANt (Boston Scientific, Inc., Natick, MA, USA) can be closed effectively, though caution is advised in these cases to ensure good compression, and abstaining from undersizing a smaller device to avoid embolization is suggested. 9 In our experience with LAA ostia measuring closer to 31 mm, closure can still be accomplished if at least two implant angles on TEE are o28 mm, and 8% to 10% compression is clearly seen with a stable tug test on a 33-mm WATCHMANt (Boston Scientific, Inc., Natick, MA, USA) device. We make an extra effort to avoid any TEE or contrast leak at implant, with the ultimate goal of obliteration of any trabeculated portion of the LAA.…”
Section: Eyeing the Futurementioning
confidence: 99%